Accuracy of a computer‐assisted planning and placement system for anatomical femoral tunnel positioning in anterior cruciate ligament reconstruction. Issue 4 (24th October 2013) - Luites, J. W. H.; Wymenga, A. B.; Blankevoort, L.; Eygendaal, D.; Verdonschot, N.
Abstract Background Femoral tunnel positioning is a difficult, but important factor in successful anterior cruciate ligament (ACL) reconstruction. Computer navigation can improve the anatomical planning procedure besides the tunnel placement procedure. Methods The accuracy of the computer‐assisted femoral tunnel positioning method for anatomical double bundle ACL‐reconstruction with a three‐dimensional template was determined with respect to both aspects for AM and PL bundles in 12 cadaveric knees. Results The accuracy of the total tunnel positioning procedure was 2.7 mm (AM) and 3.2 mm (PL). These values consisted of the accuracies for planning (AM:2.9 mm; PL:3.2 mm) and for placement (about 0.4 mm). The template showed a systematic bias for the PL‐position. Conclusions The computer‐assisted templating method showed high accuracy for tunnel placement and has promising capacity for application in anatomical tunnel planning. Improvement of the template will result in an accurate and robust navigation system for femoral tunnel positioning in ACL‐reconstruction. Copyright © 2013 John Wiley & Sons, Ltd.